How are patients' preferences for anti-TNF influenced by quality of life? A discrete choice experiment in Crohn's disease patients. (2nd November 2022) - Brunet-Houdard, Solène; Monmousseau, Fanny; Berthon, Geoffrey; Des Garets, Véronique; Laharie, David; Picon, Laurence; Fotsing, Ginette; Gargot, Dany; Charpentier, Cloé; Buisson, Anthony; Trang-Poisson, Caroline; Dib, Nina; et al.
Abstract: Background and objective: Anti-TNFs have been shown to significantly improve the health-related quality of life (HRQoL) in Crohn's disease (CD) patients. The purpose of this study was to investigate to what extend the patients' preferences for these intravenous (IV) and subcutaneous (SC) treatments differ based on respondents' quality of life. An online discrete choice experiment (DCE) was conducted to understand patient trade-offs in treatment choice. Methods: Fifty-seven Crohn's disease anti-TNF naïve patients were asked to choose between two different scenarios, considering the following attributes: mode of administration (MODE), total availability for injection (TIME), speed of onset (DELAY), risk of anti-TNF administration despite a contraindication (RISK) and total monthly out-of-pocket expenses (COST). At the same time, patients completed the IBDQ-32 questionnaire. Conditional logit models without and with interaction terms were estimated to evaluate attribute weights. Results: Patients preferred to self-administer SC anti-TNF rather than have a primary care nurse do it, whereas the preference for IV route was negative. After adding interaction terms however, the IV route became preferred for patients with impaired HRQoL, this preference having decreased as HRQoL increased. Surprisingly, patients with impaired HRQoL were less willing to spend more time on treatment, and this effect diminished as HRQoL (overall and in each dimension) became higher. Conclusions: HRQoL level changed patients' preferences for the anti-TNF treatment. The results suggest the need to optimise the management of IV infusions in the hospital and reinforce the importance of patient-reported outcome measures (PROMS) as a common practice to improve shared medical decision making.